Pengaruh Permainan Tradisional Terhadap Peningkatan Kebugaran Jasmani Pada Siswa SMPN 3 Bondowoso - Dimas Bagus Yulianto; Gatot Margisal Utomo (Jurnal Ilmiah Adiraga, 2024)
The purpose of this study was to determine the effect of traditional games on increasing physical fitness in students of SMPN 3 Bondowoso. The population in this study were students of SMPN 3 Bondowoso, totaling 38 students. The researcher planned to take a sample of 20 students of SMPN 3 Bondowoso. To determine from population to sample using random sampling technique (random / lottery). This type of research is quantitative research using quasi-experimental design. While the design or design in this study used the Non-Randomize Control Group Pretest-Posttest. The results of the analysis found that the value of sig. (2-tailed) in the experimental group is 0.009, in the control group is 0.053, so the value of sig. (2-tailed) in the experimental group > 0.05, it can be stated that traditional games have an effect on increasing physical fitness in students of SMPN 3 Bondowoso. So that the research entitled the effect of traditional games on increasing physical fitness in SMPN 3 Bondowoso students can be used as PJOK teachers to serve as a reference or guide in providing training programs or materials in particular to improve physical fitness because traditional games have been proven to improve physical fitness in SMPN students 3 Bondowoso. Keywords: traditional games, physical fitness